Effect of ultraviolet radiation on survival, infectivity and maturation of schistosoma mansonicer cariae (1990)
S. mansoni cercariae exposed to ultraviolet radiation for 1,3, 5,10 and 20 s as well as non-irradiated cercariae remained actively motile 30 min post-irradiation. Thereafter the activity decreased with increasing dose level of radiation and age of cercariae. There was no significant difference between the rates of attachment of the batches of cercariae. The recovery rates (0-49% of cercariae to which mice were exposed) of adult worms were, however, significantly different from the number of cercariae calculated to have attached to the mice (93.5-100% of cercariae to which mice were exposed). Maturation and penetration rates were dependent on radiation exposure levels. Numbers of eggs deposited in the liver of mice as well as hatchability rate of eggs varied significantly with the levels of exposure to radiation